EPISTEMOLOGI TAFSIR SUFI AL-GHAZALI DAN PERGESERANNYA - Wahyudi, Wahyudi (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
Abstract: In the history of tafsir development, there is a certain moment where there are some interactions between the Qur'an and the Sufis. Epistemologically, Sufis have a peculiar characteristic in looking at the Qur'an. The Sufis thaught that the Qur'an has two dimensions, esoteric and exoteric. These two sides are one unity and can not be separated. Al-Ghazali has its own nomenclature to refer to the áº“ahir and inner sides of the Qur'an. The esoteric and exoteric dimensions of the Qur'an in the term al-Ghazali are called â€˜ilm sadf and â€˜ilm lubÄb. The process of crossing from sadf to lubÄb involves the role of imagination in istiqÄmah suluk ilÄ AllÄh. Viewed from the perspective of epidemiological division ala Abid al-Jabiri, the epistemology of al-Ghazali include the category of 'irfÄnÄ«. But in its development al-Ghazali made a dialectic between the epistemology 'irfÄnÄ« and bayÄnÄ« at the same time, although the nuances of irfÄnÄ« still remain dominant. This research attempts to answer the problem of how the process of the dialectic epistemology of al-Ghazali and how its building style. This kind of dialectic is one of al-Ghazali effort to built the harmonization between sadf science which tends to bayÄnÄ« with the science of lubÄb which tend to irfÄnÄ«. Clearly, the process of this dialectic can be seen in one of his works IhyÄâ€™ 'UlÅ«m al-DÄ«n. This research uses the qualitative method and includes library research. Abstrak: Â Dalam sejarah perkembangan tafsir, ada momen tertentu saat terjadi interaksi antara al-Qurâ€™an dan kaum Sufi. Secara epistemologis, para Sufi meÂmiliki ciri khas dalam memandang al-Qurâ€™an. Kaum Sufi memandang bahwa Qur'an memiliki dua dimensi, esoterik dan eksoteris. Dua dimensi ini merupakan satu kesatuan dan tidak dapat dipisahkan. Al-Ghazali memiliki nomenklatur tersendiri untuk menyebut sisi áº“ahir dan baá¹in al-Qurâ€™an. Dimensi esoterik dan eksoterik al-Qurâ€™an dalam istilah al-Ghazali disebut dengan â€˜ilm sadf dan â€˜ilm lubab. Proses penyebrangan dari sadf ke lubÄb ini melibatkan peran khayal dengan cara istiqÄmah suluk ilÄ Allah. Ditinjau dari perspektif pembagian epistemologi ala Abid al-Jabiri, epistemologi al-Ghazali masuk dalam kategori â€˜irfÄnÄ«. Namun dalam perkembangannya al-Ghazali melakukan dialektika antara epistemologi â€˜irfÄnÄ« dan bayÄnÄ« secara bersamaan, meskipun nuansa â€˜irfÄnÄ« masih tetap dominan. Penelitian ini berupaya untuk menjawab rumusan masalah bagaimana proses dialektika epistemologi al-Ghazali dan bagaimana corak bangunannya. Dialektika ini merupakan upaya harmonisasi al-Ghazali antara ilmu sadf yang cenderung bayÄnÄ« dengan ilmu lubab yang mendekati â€˜irfÄnÄ«. Secara jelas proses dialektika ini dapat dilihat dalam salah satu karyanya IhyÄâ€™ UlÅ«m al-DÄ«n. Penelitian ini menggunakan metode kualitatif dan merupakan penelitian kepustakaan.